Accidents in the construction industry in the state of Paraíba (2017 - 2022) - Farias, Fábio Aquilino de; Lucena, Susana Cristina Batista; Lima Neto, Inácio Alves de (Brazilian Journal of Production Engineering, 2025)
Brazil is one of the countries that ranks first in the records of situations that cause permanent disability, also ranking fifth in the records of deaths due to accidents. This fact can be associated with the functions performed and the risk agents present in the work sector. In 2022, 612.9 thousand accidents were recorded with 2.5 thousand death notifications. Also in that year, 148.8 thousand sick leave benefits were granted, as well as 6.5 thousand disability retirement benefits, generating an impact of approximately 88.3 billion reais. Among these records, 9,229 accidents stand out in the building construction sector in Brazil, with 2,595 absences in the same sector. The study was documentary research of a statistical nature on the records of work accidents in the state of Paraíba between the years 2017 and 2022, according to the Occupational Health and Safety Observatory of the Ministry of Labor and Employment. At the end of this study, it can be concluded that the profile of work accidents observed in the state of Paraíba in recent years, in the construction sector, revolves around typical work situations, generating material and human losses, with injuries, mainly, in the extremities of the limbs, partially or totally incapacitating workers. It was also concluded that the Building Technician is an important part of safety management, being a substitute for the Safety Technician when the latter is dismissed and must have knowledge about Safety at Work.